Produção de ácidos graxos voláteis por biodigestão anaeróbia da manipueira - Giongo, Citieli (2011)
The cultivation of cassava extends throughout Brazil because of its excellent adaptation to different soils and climatic conditions. Our country occupies the second position at the worldwide ranking in cultivating this plant (15% of the world production). The industrial processing of cassava generates a liquid waste, the so called manipueira, considered as a pollutant due to the high organic load and it contains a cyanogenic glycoside, which can be hydrolyzed to cyanide. One way to minimize environmental impacts and to aggregate value to the effluent is its use in the production of volatile fatty acids (VFA) via anaerobic fermentation, which was the main goal of this study, performed using manipueira as a substrate and inoculum of swine dejection. The fermentation process during the production of VFA is characterized as a result of the activity of acidogenic bacteria, by the pH decrease and increased hydrolysis and acidification of the organic matter. Inoculum of swine and of bovine dejections were tested in synthetic medium at 30°C and initial pH of 7.0, to define the most appropriate inoculum for the production of volatile fatty acids, swine dejection presented the best results and was used in posterior fermentations. Besides the parameter of VFA production, the behavior of pH, alkalinity and acidity were as well monitored in all experiments. In the fermentation performed with manipueira as a substrate, glucose was used as the main carbon source and different concentrations were tested (1, 2, 5 and 9 g/L) and it was observed that the concentration of 2 g/L of glucose produced about 2.5 g/L of VFA, expressed as acetic acid, after 36h and at pH 5.0, this concentration of glucose was used in further experiments. The alkalinity and temperature levels were tested by experimental design, in which at 30°C with 3 g/L of sodium bicarbonate better conditions were observed, resulting in the production of 3.4 g/L of VFA in 45h. On the basis of these conditions, the model for the production of VFAs was validated by performing fermentations in triplicate and evaluating the reproducibility of the process. There were minor variations between replicates, as assessed by the low relative standard deviation (RSD) from the mean value of the results. The highest production of volatile fatty acids in this experiment was obtained at 45h with an average of VFAs production of 3.4 g/L, with RSD of 1.4% and pH 5.6. The chemical oxygen demand (COD) and the amount of cyanide in manipueira were analyzed being 8865 mg/L of O2 and 1.9 mg/L, respectively, among other physical and chemical characteristics that were determined. After the anaerobic fermentation process, a reduction of 21.6% of COD amount and 12.9% of cyanide amount were obtained, indicating that the production of VFAs not only aggregates value to the manipueira but also contributes to the reduction of important contaminants.